The Use Of Mediation As An Alternative Dispute Resolution In The Settlement Of Investment Disputes - Gayo, Sabela (International Asia Of Law and Money Laundering (IAML), 2024)
Investment or investment has a very important function regarding will improve the development of the state of the country's economy. This investment is an activity carried out by the business world in order to improve people's living standards. The purpose of this study is to determine how the forms of dispute resolution in domestic investment according to Law No. 25 of 2007 and how the obligations and responsibilities of investors. By using normative juridical research methods concluded: the form of domestic investment dispute resolution according to Article 32 of Law No. 25 of 2007 is through deliberation and consensus; arbitration, Alternative Dispute Resolution, courts, and especially between disputes between governments and foreign investment, disputes are resolved through international arbitration that has been agreed. According to Article 15 of Law Number 25 of 2007, the obligation of investors in Indonesia is to apply the principles of good corporate governance, carry out corporate social responsibility (corporate social responsibility)while the responsibility of investors is regulated in Article 16, namely: ensuring the availability of capital from sources that do not conflict with the provisions of laws and regulations; to bear and settle any liability for losses if the investor ceases or abandons or abandons business activities unilaterally in accordance with the provisions of applicable laws and regulations; to create a healthy competitive business and to prevent practices. Investment mediation is the right choice because mediation is the spirit of local Indonesian stakeholders in resolving disputes and currently the international community is applying it as evidenced by ICSID offering wide access to mediation with countries, State entities or REIOS related to investment.